The Problem of the Ontology of Law between Vocation to the System and Teleological Rationality (Itinera, 2015)
This paper aims to address the problem of the ontology of law investigating the foundation of the systematic nature that belongs to it as a legal system bearer of an “order”. For this purpose, taking in a comparative consideration three different models, the positivism, the axiological-constitutional one and the classical-metaphysical one, subjects such as the person, the teleological rationality and the natural law are analyzed and discussed in their foundational value and in their specific function.